2003
DOI: 10.1002/ajmg.a.10634
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing the mechanisms of origin of de novo short‐arm duplications of chromosome 9

Abstract: Three de novo short-arm duplications of chromosome 9 were investigated by fluorescence in situ hybridization (FISH) and genotyping of microsatellite loci with the aim of disclosing their mechanisms of origin. Two of these duplications were identified as direct and one as an inverted duplication, and they comprised nearly the entire 9p. In the two dirdup(9p), the distal breakpoints were mapped to subtelomeric sequences, whereas the proximal break boundaries were defined by pericentromeric sequences. The materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…However, most of these reported duplications are due to malsegregation of chromosomes inherited from a parent with a reciprocal translocation involving chromosome 9, with relatively few pure 9p duplications arising de novo [Chiyo et al, 1976; Baccichetti et al, 1979; Fryns et al, 1979; Motegi et al, 1985; Mattina et al, 1987; Haddad et al, 1996; Fujimoto et al, 1998; Tsezou et al, 2000; Bonaglia et al, 2002; Krepischi-Santos and Vianna-Morgante, 2003; Swinkels et al, 2008]. Despite varying sizes of duplicated chromosomal segments, there is a significant overlap in clinical features in duplication 9p syndrome, which is attributed to the terminal segment of 9p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of these reported duplications are due to malsegregation of chromosomes inherited from a parent with a reciprocal translocation involving chromosome 9, with relatively few pure 9p duplications arising de novo [Chiyo et al, 1976; Baccichetti et al, 1979; Fryns et al, 1979; Motegi et al, 1985; Mattina et al, 1987; Haddad et al, 1996; Fujimoto et al, 1998; Tsezou et al, 2000; Bonaglia et al, 2002; Krepischi-Santos and Vianna-Morgante, 2003; Swinkels et al, 2008]. Despite varying sizes of duplicated chromosomal segments, there is a significant overlap in clinical features in duplication 9p syndrome, which is attributed to the terminal segment of 9p.…”
Section: Discussionmentioning
confidence: 99%
“…In most of these patients, the duplication 9p is a result of an abnormal chromosome segregation of a balanced translocation in one of the parents [Baccichetti and Tenconi, 1973; Wajntal et al, 1985]. De novo duplications of this chromosomal region have been previously described in approximately 15 patients [Chiyo et al, 1976; Baccichetti et al, 1979; Fryns et al, 1979; Motegi et al, 1985; Mattina et al, 1987; Haddad et al, 1996; Fujimoto et al, 1998; Tsezou et al, 2000; Krepischi-Santos and Vianna-Morgante, 2003]. Patients with partial trisomy of the short arm of chromosome 9 often display a wide spectrum of clinical symptoms including developmental delay, craniofacial abnormalities (bulbous nose, hypertelorism, downward-slanting palpebral fissures), limb abnormalities (short fingers and toes with small nails, fifth-finger clinodactyly) and skeletal malformations.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases the structural rearrangements were maternal in origin. Three de novo duplications of chromosome 9p were studied and two found to be maternal and one paternal in origin, the latter possibly due to a post-zygotic error (Krepischi-Santos et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The high frequency of the partial trisomy 9p may indicate a particular breakpoint sensitivity of one or more Achkar et al, 2010]. Previous studies have found that dup(9p) could be the result of the recombination events between homologous repeats in this region [Krepischi and Vianna, 2003]. Clinical severity in trisomy 9p generally correlates with the extent of the trisomic chromosome region; duplication of 9pterp11 is associated with milder dysmorphism, whereas duplication of 9p21.1q22-32 is associated with more severe craniofacial features [Stagi et al, 2014].…”
Section: Discussionmentioning
confidence: 99%